2017
DOI: 10.1080/1331677x.2017.1305785
|View full text |Cite
|
Sign up to set email alerts
|

Energy use, CO2 emissions and economic growth – causality on a sample of SEE countries

Abstract: The primary aim of this study is to examine the causal relations between energy use, CO 2 emissions and economic growth, using the examples of Greece and Bulgaria. The empirical evidence on South Eastern Europe (SEE) considering this research is quite sparse, so there is merit in the analysis of the paper. Vector Error Correction model with annual data from 1980 to 2010 has been used in order to determine potential causality between the variables. The empirical findings indicate that, in the long run there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 41 publications
(37 reference statements)
4
27
0
1
Order By: Relevance
“…Cointegration test shows that there is a long-run relationship between the variables in both countries. This result is similar to Bozkut and Akan (2014), Obradovic and Lojanica (2017), Oduloru and Chinedu (2009), Chebbi and Boujelbebe (2008) and few others as stated in the literature. For importing countries, empirical results show that carbon dioxide emissions affected by the energy consumption and economic growth in the short-run.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Cointegration test shows that there is a long-run relationship between the variables in both countries. This result is similar to Bozkut and Akan (2014), Obradovic and Lojanica (2017), Oduloru and Chinedu (2009), Chebbi and Boujelbebe (2008) and few others as stated in the literature. For importing countries, empirical results show that carbon dioxide emissions affected by the energy consumption and economic growth in the short-run.…”
Section: Resultssupporting
confidence: 91%
“…Based on data from 1971-2004 for six Central American countries and found that there is a positive relationship between energy and CO 2 emissions. Obradovic and Lojanica (2017), Odularu and Chinedu (2009) and Chebbi and Boujelbebe (2008) found evidence of a long-run relationship between energy consumption and economic growth. These results are similar to Naser (2015) and Chen et al (2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Energy consumption leads to significantly increased carbon emissions. A great number of studies have sought to examine the relationship between energy use and carbon emissions while analyzing the EKC hypothesis (see Ahmad, Hengyi [9], Rahman, CAI [10], Obradović and Lojanica [11], Mohiuddin, Asumadu-Sarkodie [12], Wang, Chen [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Most investigators [29] revealed diverse type of linkage between environmental emanations and economic development utilizing factors like CO 2 discharge nitrous oxide and sulfur dioxide to quantify air contamination and GDP to gauge economic growth.…”
Section: Methodsmentioning
confidence: 99%